Relationship between socioeconomic factors, distribution of public access defibrillators and incidence of out-of-hospital cardiac arrest. (May 2019) - Dicker, Bridget; Garrett, Nick; Wong, Samuel; McKenzie, Helen; McCarthy, John; Jenkin, Gareth; Smith, Tony; Skinner, Jonathan R.; Pegg, Tammy; Devlin, Gerry; Swain, Andrew; Scott, Tony; et al.
Abstract: Background: Survival from out-of-hospital cardiac arrest (OHCA) is improved when public access defibrillators are used. Areas of socioeconomic deprivation may have higher rates of OHCA and thus a greater demand for public access defibrillators. We aimed to determine if there was a relationship between socioeconomic factors, the geographic distribution of public access defibrillators (PADs) and incidence of OHCA. Method: Socioeconomic deprivation data was obtained from the Census-based 2013 Index of Deprivation. Spatial information for PADs was obtained from a New Zealand PAD database (AED Locations) in 2016 and 2018. Location data for OHCA was obtained from the St John New Zealand OHCA registry for the period 1 October 2013 to 30 June 2016. Relationships between these variables were analysed using a Poisson regression analysis. Results: Cardiac arrest incidence increased with increasing deprivation. The incidence in the most deprived areas of 156.5 events per 100, 000 person years (135.4–180.9, 95% CI) is double the incidence in the least deprived areas at 78.0 events per 100, 000 person years (66.4–91.7, 95% CI). Significant increases in the rates of OHCA were observed with every 1% increase in proportions of Māori (1.0%, 0.61–1.4%, 95% CI, p = 0.001), Pacific Peoples (0.6%, 0.21–0.9%, p = 0.005), >65 year olds (3.7%, 3.0–4.3%, p < 0.001), and males (3.7%, 1.8–5.6%, p < 0.001). In 2018, the decile 10 areas had the lowest coverage of PADs (65% of these areas contained a PAD) compared with less deprived areas (68–84%, median 81%). Conclusions: The most socioeconomically deprived communities had the highest incidence of OHCA and the least availability of PADs. This provides impetus for targeted PAD placement in areas of higher deprivation.